Investigation of Permanent Deformation in Iraqi Highways- Iraqi Expressway No.1 as a Case Study - Mutleg, Ammar; Al-Sharrad, Muayad A.; Abd, Duraid (Iraqi Journal of Civil Engineering, 2023)
Pavement rutting as a permanent deformation is a major type of distress in flexible pavements. In Iraq, the rutting in Expressway pavements represents a severe problem due to its widespread, and high severity and distress density levels. Therefore, driving is profoundly dangerous and causes severe damage to the vehicle’s parts and the life of its riders. To date, the number of comprehensive research on pavement rutting has been limited in Iraq, owing to several technical, logistic, and economic considerations. The current research studies the major mechanisms responsible for rutting and evaluates the structure of the Iraqi Expressway No.1 at selected sections. The work encompasses field and laboratory aspects. The field work involved; performing field surveys to investigate the pavement rutting condition and its extension with depth, characterizing pavement layers in terms of geometric material properties, and collecting field samples for lab tests. The laboratory work was detailed and included; performing a set of standard lab tests on samples taken from the asphalt, the subbase, and the subgrade layers as well as the natural ground. In addition, the project’s archive was searched for specific design information and limitations. In order to assess pavement rutting in the selected sections of Expressway No.1/R9 (A and B), two well-established evaluators were considered; The rutting severity levels and the distress density.